Patterns of Eating Behavior and Nutritional Status in University Students after Two Years of Online Education - Héctor Fuentes Barría; Raúl Aguilera Eguía; Catalina González Wong (Revista Finlay, 2022)
Background: the university student population is particularly vulnerable to acquiring unhealthy eating behaviors, as a result of factors such as inadequate nutrition and the high sedentary lifestyle generated by the high academic load and little free time, the result of which leads to potential health risks. Objective: to describe and compare the pattern of eating behavior and nutritional status in sixth-year students of the dentistry degree taught by the Andrés Bello University at the Concepción campus after two years of online education due to COVID-19. Methods: a descriptive cross-sectional study was carried out. The sample consisted of 18 university students with an average age of 24.94 ± 1.95 years classified as eutrophic (21.92 ± 1.27 km/m2) and overweight (28.13 ± 1.53 km/m2). m2) both groups presenting sufficient eating habits (12.27 ± 1.43 points). The Survey of Behaviors and Eating Habits in Higher Education was applied and a comparison was made between groups according to nutritional status determined by the body mass index. The descriptive analysis used the measures of central tendency and dispersion, mean, standard deviation, minimum and maximum. The distribution and homoscedasticity of the data was determined using the Shapiro-Wilk and Levene test. The comparison between groups was carried out with the Student's t-test for independent samples, considering an alpha level of significance <0.05 for all analyses. . Results: significant mean differences between groups were only observed for food concerns (p= 0.009). Conclusion: food concern suggests an interest in self-care. Other studies are required that explain all the modulating variables of eating behavior with the aim of promoting university spaces that lead to awareness of healthy lifestyles after two years of online higher education as a result of the COVID-19 pandemic.